2023
DOI: 10.1021/acsami.2c19058
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinting Using Synovium-Derived MSC-Laden Photo-Cross-Linked ECM Bioink for Cartilage Regeneration

Abstract: In this study, inspired by the components of cartilage matrix, a photo-cross-linked extracellular matrix (ECM) bioink composed of modified proteins and polysaccharides was presented, including gelatin methacrylate, hyaluronic acid methacrylate, and chondroitin sulfate methacrylate. The systematic experiments were performed, including morphology, swelling, degradation, mechanical and rheological tests, printability analysis, biocompatibility and chondrogenic differentiation characterization, and RNA sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…For example, Sang et al presented a photo-cross-linked ECM bioink composed of modified proteins and polysaccharides, including gelatin methacrylate, hyaluronic acid methacrylate, and chondroitin sulfate methacrylate. The results indicated that the photo-cross-linked ECM hydrogels possessed a suitable degradation rate and excellent mechanical properties, and the 3D bioprinted ECM scaffolds obtained favorable shape fidelity and effectively promoted cartilage regeneration ( Sang et al, 2023 ). Bioceramics are often combined with natural or synthetic polymers to prepare 3D printable bioinks, which are more widely used in OC tissue engineering.…”
Section: Classification Of Oc Scaffoldsmentioning
confidence: 99%
“…For example, Sang et al presented a photo-cross-linked ECM bioink composed of modified proteins and polysaccharides, including gelatin methacrylate, hyaluronic acid methacrylate, and chondroitin sulfate methacrylate. The results indicated that the photo-cross-linked ECM hydrogels possessed a suitable degradation rate and excellent mechanical properties, and the 3D bioprinted ECM scaffolds obtained favorable shape fidelity and effectively promoted cartilage regeneration ( Sang et al, 2023 ). Bioceramics are often combined with natural or synthetic polymers to prepare 3D printable bioinks, which are more widely used in OC tissue engineering.…”
Section: Classification Of Oc Scaffoldsmentioning
confidence: 99%
“…rabbit, goat, porcine) and included in the bioink at a typical cell density ranging between 1 × 10 7 and 2 × 10 7 cells/mL [ 91 – 95 ]. In contrast, Sang et al [ 96 ] proposed synovium-derived MSCs (used at a lower cell density of 1 × 10 6 cells/mL) as a promising alternative, thanks to their high ability of proliferation and chondrogenic differentiation, promoted by the high expression of CD44 and CD105 receptors of these cells.…”
Section: In Vivo Advances In the 3d Bioprinting Of Cartilagementioning
confidence: 99%
“…GeL-based bioinks are usually made by physically mixing GeL or GelMA with other components to achieve optimal mechanical properties [ 91 – 93 , 97 ]. For example, GelMA has been combined with other methacrylated polysaccharides, such as HAMA and chondroitin sulphate methacrylate (CSMA), or with Alg and Alg sulphate to form interpenetrating networks by combining UV-mediated chemical cross-linking with Ca 2+ ion–mediated physical gelation [ 93 , 96 ].…”
Section: In Vivo Advances In the 3d Bioprinting Of Cartilagementioning
confidence: 99%
“…In recent years, the advent of 3D bioprinting has brought about a revolutionary shift in the tissue engineering landscape. This cutting-edge technology allows the precise creation of sophisticated tissues that closely replicate the structural and functional aspects of native tissues. Despite their tremendous potential, the translation of bioprinting techniques into clinical applications has encountered several challenges. The key requirements for clinical viability include ensuring biocompatibility, pro-healing properties, spatial control, reliable fabrication, implantation feasibility, and accessibility. A novel strategy known as in situ bioprinting has emerged to address these challenges and push the boundaries of clinical translation …”
Section: Introductionmentioning
confidence: 99%